2022
DOI: 10.1177/01945998221083097
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Squamous Cell Carcinoma Survival Outcomes Following Induction Chemotherapy vs Standard of Care Therapy

Abstract: Objective To compare oncologic outcomes in sinonasal squamous cell carcinoma (SNSCC) treated with standard of care (SOC) definitive therapy, consisting of surgery or chemoradiotherapy, vs induction therapy followed by definitive therapy. Study Design Retrospective review. Setting Academic tertiary care hospital. Methods The medical records of patients with biopsy-proven SNSCC treated between 2000 and 2020 were reviewed for demographics, tumor characteristics, staging, treatment details, and oncologic outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…19 Murr et al demonstrated 3-year OS improvement with induction chemotherapy. 20 Su et al found lower survival rates in radiotherapy and surgery groups compared with multimodality therapy. 21 Keerio et al compared modalities for maxillary SCC, finding adjuvant and neoadjuvant multimodal therapy yielded better outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Murr et al demonstrated 3-year OS improvement with induction chemotherapy. 20 Su et al found lower survival rates in radiotherapy and surgery groups compared with multimodality therapy. 21 Keerio et al compared modalities for maxillary SCC, finding adjuvant and neoadjuvant multimodal therapy yielded better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Farrell et al (NCDB) showed induction chemotherapy followed by surgery improved OS compared to other approaches 17 . Murr et al demonstrated 3-year OS improvement with induction chemotherapy 18 . Su et al found lower survival rates in radiotherapy and surgery groups compared to multimodality therapy 19 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Several case series have investigated IC only in advanced SNSCC, finding an overall survival benefit when surgery was included as a potential definitive treatment. 23 Within these This article is protected by copyright. All rights reserved.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These recommendations are based upon one systematic review 2 (level 2) and four retrospective cohort studies 1,3–5 (level 3).…”
Section: Level Of Evidencementioning
confidence: 99%
“…Most recently, Murr et al performed a matched analysis of patients with locally advanced sinonasal SCC who received either IC or upfront definitive therapy with primary surgery or CRT. 5 IC included platins (100%) and taxanes (77%), with carboplatin + paclitaxel + cetuximab being the most common (62%) regimen. Overall, 85% responded to IC and 23% experienced adverse events, including neutropenia, type I hypersensitivity, and acute kidney injury.…”
Section: Literature Reviewmentioning
confidence: 99%